Social responsibility in the university and quality of administrative service - Pumacayo Palomino, Ilich Ivan (2020)
This study was aimed to determine the relationship between university social responsibility and quality of administrative services at the university. It was hypothetical deductive method, being a basic, transversal correlational research, non experimental design. The present sample was probabilistic, consisting of 268 students; using the survey and the questionnaire. The study concluded that there is a significant relationship between the variable social responsibility of the university and the quality of the administrative service in the university; This implies stating that: the higher the social responsibility of the university, the higher the levels of quality of the administrative service.